Optimizing Diabetes Management - Vinall, Maria; Sinclair, Heather Q. (MD Conference Express, 2010)
Cardiovascular disease (CVD) is one of the primary clinical risks that are associated with type 2 diabetes. While a clear graded association of CVD risk has been noted with hyperglycemia, the role of glucose control in CVD risk mitigation remains uncertain. This article discusses data from the UK Prospective Diabetes Study [UKPDS] Group, the relationship between atherosclerosis and diabetes, the ARBITER 6-HALTS Trial, and blood glucose control by sulphonylureas or insulin.